Recherche sur la violence familiale : contribution des différentes épistémologies - Poulin, Carmen; Ross, Lynda (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1997)
Knowledge, over the last century, has been grounded mainly in the institution of empirical science. This epistemological tradition is tightly linked to positivism and objectivity. Feminists from various disciplines, including that of Criminology, have become disillusioned in the ability of traditional empiricism to produce knowledge that is relevant, historically and socially, to women, and based in their everyday experience. Feminists have proposed alternative epistemological frameworks to explore questions driven by political feminist agendas. In the present article, an overview of these new epistemological frameworks is presented to develop an evaluation grid. Using this grid, studies from different traditions in the area of family violence and violence against women are examined and critiqued to determine how each epistemological framework can advance (or not) the feminist agenda.